Effects of aging on liver microcirculatory function and sinusoidal phenotype - Raquel Maeso‐Díaz; Martí Ortega‐Ribera; Anabel Fernández‐Iglesias; Diana Hide; Leticia Muñoz; Amelia J. Hessheimer; Sergi Vila; Rubén Francés; Constantino Fondevila; Agustı́n Albillos; Carmen Peralta; Jaime Bosch; et al. (2018)
Abstract The socioeconomic and medical improvements of the last decades have led to a relevant increase in the median age of worldwide population. Although numerous studies described the impact of aging in different organs and the systemic vasculature, relatively little is known about liver function and hepatic microcirculatory status in the elderly. In this study, we aimed at characterizing the phenotype of the aged liver in a rat model of healthy aging, particularly focusing on the microcirculatory function and the molecular status of each hepatic cell type in the sinusoid. Moreover, major findings of the study were validated in young and aged human livers. Our results demonstrate that healthy aging is associated with hepatic and sinusoidal dysfunction, with elevated hepatic vascular resistance and increased portal pressure. Underlying mechanisms of such hemodynamic disturbances included typical molecular changes in the cells of the hepatic sinusoid and deterioration in hepatocyte function. In a specific manner, liver sinusoidal endothelial cells presented a dysfunctional phenotype with diminished vasodilators synthesis, hepatic macrophages exhibited a proinflammatory state, while hepatic stellate cells spontaneously displayed an activated profile. In an important way, major changes in sinusoidal markers were confirmed in livers from aged humans. In conclusion, our study demonstrates for the first time that aging is accompanied by significant liver sinusoidal deregulation suggesting enhanced sinusoidal vulnerability to chronic or acute injuries.